(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article analyzes the textual (textological) problems of Abai Kunanbayuly’s literary heritage and examines scholarly approaches to restoring the authenticity of the poet’s original texts. The relevance of the study lies in the numerous textual distortions found in various editions of Abai’s poetry and prose published in different historical periods, which significantly influence the interpretation of their meaning and ideological content. The research is primarily based on Kayim Mukhamedkhanov’s fundamental work «On the Textology of Abai’s Works». A comparative analysis is conducted between Murseit Bikeyuly’s manuscripts (1905-1910), the first printed collection of Abai’s works published in 1909, and later Soviet-era editorial versions. The article presents concrete examples of textual discrepancies in several poems. It substantiates that «Internatta okyp jur» («Studying at a Boarding School») and «Gylym tappai maktanba» («Do Not Boast Without Knowledge») were originally parts of a unified work. In the poem «Zhaz» («Summer»), the misprinted line «Azildesip, sylkyldap» is corrected to the authentic version «Kenesip, kulip, sylqyldap». Lexical, phonetic, and semantic inaccuracies in works such as «Bolys boldym, mineki», «Bireudin kisisi olse, karaly ol», and «Aittym salem, Kalamkas» are also analyzed based on Mukhamedkhanov’s arguments. The study further reviews contemporary English-language research on Abai’s textology, including issues of digital corpus creation, orthographic and phonetic variation among manuscripts, and interpretative challenges related to the «Words of Edification». The findings confirm that restoring Abai’s authentic texts is essential for preserving the historical memory of national spirituality. Mukhamedkhanov’s methodology laid the foundation for a new direction in Kazakh literary studies and remains central to modern Abai studies.